Effects of TiO2 Properties on Performance of CH3NH3PbI3 Perovskite Photovoltaic Cells. Issue 47 (19th April 2016) - Adli, Hasyiya K.; Harada, Takashi; Ito, Seigo; Nakanishi, Shuji; Ikeda, Shigeru
ABSTRACT: The effects of TiCl4 post-treatment on the physicochemical properties of porous TiO2 ( p TiO2 ) layers fabricated at 300 °C and 400 °C (denoted as p TiO2 (300) and p TiO2 (400), respectively) in CH3 NH3 PbI3 perovskite photovoltaic cells were investigated. Water contents (physisorbed water and water derived from surface hydroxyl groups) of p TiO2 (300) and p TiO2 (400) before and after TiCl4 post-treatment were measured by using temperature desorption spectroscopy (TDS). Moreover, structural analysis of the CH3 NH3 PbI3 perovskite part was performed by X-ray diffraction (XRD). In the case of p TiO2 (300), the content of water was increased by the TiCl4 post-treatment due to the removal of residual organic compounds that existed before the treatment. It then caused a change in the surface activity of p TiO2 (300) and enhancement of solar cell performance and photocurrent density, though suppression of CH3 NH3 PbI3 perovskite formation occurred. In comparison, contents of water were decreased for p TiO2 (400), leading to enhancement of the conversion of PbI2 to CH3 NH3 PbI3 perovskite. As a result, there were significant increases in short circuit current density (Jsc s) and PCEs. The results showed that TiCl4 post-treatment is an effective approach to prepare high-performance CH3 NH3 PbI3 perovskite solar cells without heat treatment at a very high temperature.